Ioligtiogsarmoede: 'n Christelik etiese refleksie - Britz, J. J. (Verbum et ecclesia, 2001)
Information poverty does not only pertain to the lack of essential information, but can also be defined as a condition of life where the majority of people within a specific context do not have the means nor the skills to access essential information for survival and development. It is a form of poverty that is furthermore characterised by global social injustice, and can as such be seen as one of the major poverty problems facing the new millenium. This article investigates the problem of information poverty from a moral perspective, and suggests ethical guidelines to address this form of poverty.